Comparative Analysis of Fluorine‐Directed Glycosylation Selectivity: Interrogating C2 [OH → F] Substitution in d‐Glucose and d‐Galactose (Eur. J. Org. Chem. 32/2015). Issue 32 (November 2015) - Santschi, Nico; Gilmour, Ryan
Abstract : The cover picture shows the iconic hat and pipe of the detective Sherlock Holmes, to reflect the investigative nature of this study. By interrogating the reactivity of two closely similar glycosyl donors, it was possible to probe the effect of molecular editing at C2 (OH to F) and C4 (glucose and galactose) on the entropic and enthalpic reaction parameters of glycosylation. Details are discussed in the Short Communication by N. Santschi and R. Gilmour on6439 ff .